ANALISIS FAKTOR PENGARUH PENDAPATAN BANK BERDASARKAN INTEREST INCOME DAN FEE BASED INCOME (STUDI PADA BANK PERSERO 2005-2014) - Anindyntha, Firdha Aksari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
Bank as financial institutions perform traditional and non traditional activities. Traditional activities related to the intermediation function of banks collecting and releasing funds to people who earn income in the form of interest. While non-traditional ktivitas may include the provision of other financial services are getting returns in the form of fee-commonly referred to as non-interest income (fee-based income). Banks earned income of banks is essential to ensure the sustainability and the health of banks. Thus, this study wanted to know the factors that affect interest income and fee-based income. This study uses panel data regression and model chosen is the Fixed Effects Model (FEM). Variable LDR, deposits, and net income positive significant effect on the interest income. The only variable that was not significant NPL against interest income. Further to the variable equity and net income has a significant positive effect on fee-based income. While e- banking variables have a significant influence in a negative direction and variable assets no significant effect on fee-based income.Â Kata kunci: Interest Income, Fee Based Income, LDR, NPL, DPK, Asset, Equity, Net Income, E- bankingÂ Â